Pediatric Critical Care in Resource-Limited Settings—Overview and Lessons Learned - Slusher, Tina M.; Kiragu, Andrew W.; Day, Louise T.; Bjorklund, Ashley R.; Shirk, Arianna; Johannsen, Colleen; Hagen, Scott A. (Frontiers in Pediatrics, 2018)
Pediatric critical care is an important component of reducing morbidity and mortality globally. Currently, pediatric critical care in low middle-income countries (LMICs) remains in its infancy in most hospitals. The majority of hospitals lack designated intensive care units, healthcare staff trained to care for critically ill children, adequate numbers of staff, and rapid access to necessary medications, supplies and equipment. In addition, most LMICs lack pediatric critical care training programs for health care providers or certification procedures to accredit healthcare providers working in their pediatric intensive care units (PICU) and high dependency areas. Pediatric intensive care units can improve the quality of pediatric care in general and, if properly organized, can effectively treat the severe complications of high burden diseases such as diarrhea, severe malaria, and respiratory distress using low-cost interventions. Setting up a PICU in a LMIC setting requires planning, specific resources, and most importantly investment in the nursing and permanent medical staff. A thoughtful approach to developing pediatric critical care services in LMICs starts with fundamental building blocks: training healthcare professionals in both skills and knowledge, selecting resource appropriate effective equipment, and having supportive leadership to provide an enabling environment for appropriate care. If these fundamentals can be built on in a sustainable manner, an appropriate critical care service will be established with the potential to significantly decrease pediatric morbidity and mortality in the context of public health goals as we reach toward the Sustainable Development Goals.